Relationships Among Pre-Pregnancy BMI, Gestational, and Postpartum Oral Glucose Tolerance Results in Women With Gestational Diabetes Mellitus - Mi, Chunmei; Liu, Hong; Peng, Hongying; Cheng, Chunxia; Wang, Meng; Liu, Hua; Feng, Guo; Wu, Jinru; Nie, Hao; Liu, Min (Frontiers in Nutrition, 2021)
Background and Aims: To investigate the relationship among maternal demographic and clinical characteristics, gestational and postpartum oral glucose tolerance test (ppOGTT) results in patients with gestational diabetes mellitus (GDM). Methods: Patients with gestational diabetes mellitus from January 1, 2016, to August 31, 2019, were enrolled. General characteristics, dietary energy intake, pre-gestational body mass index (BMI), gestational oral glucose tolerance test (gOGTT), and 42 days ppOGTT results of all participants were collected. The relationships among maternal clinical characteristics, fasting glucose of gOGTT (gOGTT-FPG), 1 h postprandial glucose of gOGTT (gOGTT-1h PG), 2 h postprandial glucose of gOGTT (gOGTT-2h PG), and maternal postpartum glucose outcomes were evaluated. Results: A total of 156 patients with GDM were included in this study. Among them, 73.7% had inadequate daily total energy intake, an insufficient ratio of carbohydrates and protein, and an excessive fat ratio. Most of the patients (81.4%) were normal in their ppOGTT examination. Less than 20% of the patients (16.7%) were in the pre-diabetic situation, and 3 patients (1.9%) had diabetes. Pre-pregnancy BMI of patients with GDM was a risk factor for increased gOGTT-FPG levels. Those who were overweight before pregnancy had a greater risk for a higher gOGTT-FPG compared to those who had normal pre-pregnancy BMI (P = 0.021, odds ratio [OR] = 4.583). Abnormal gOGTT-2hPG was a risk factor for abnormal ppOGTT (P = 0.04). Those who had an elevated gOGTT-2hPG (≧8.5 mmol/L) had a 2.426 times higher risk for abnormal ppOGTT than those who had normal gOGTT-2hPG (<8.5 mmol/L) results. Conclusion: For women who are overweight before pregnancy, it is better to control their BMI to normal before getting pregnant. Women who had abnormal gOGTT-2h PG should pay more attention to the ppOGTT results.